Using simulation to uncover care aides physiological and emotional responses to their work: A research protocol - Patricia Morris; Rose McCloskey; Karen Furlong; Jennifer Moore (PLoS ONE, 2025)
Care aids play a vital role in long-term care homes by providing essential support to residents, assisting with daily activities, and ensuring that individuals receive the care and attention they need. These professionals are often the primary point of contact for residents, making their well-being a crucial aspect of long-term care. However, the demanding nature of the job can lead to high levels of stress, and job dissatisfaction. While much is known about the antecedents to stress and subjective experiences of job-stress in LTC, there has been limited research to quantify the mental workload of that work. This paper describes the protocol for our research project that will use simulation to measure the mental workload of care aides while they conduct routine care to residents. Specifically, study participants will take part in simulation involving caring for a resident with dementia, which entails common challenges encountered by care aides including time pressure and resistance to care. Mental workload will be measured using physiological responses including heart rate, heart rate variability, and pupil diameter. This research promises to extend existing knowledge on care aides’ experiences and provide a deeper, multidimensional understanding of stress and mental well-being in caregiving roles. This innovative approach will not only validate qualitative insights but also uncover new dimensions of care aides’ work that may have been overlooked, paving the way for more targeted interventions and support strategies in the workplace.